An appraisal of crustal structure of the Indo-Burmese subduction region. (June 2019) - Saikia, Sowrav; Baruah, Santanu; Chopra, Sumer; Gogoi, Bibhuti; Singh, Upendra K.; Bharali, Bubul
Highlights: The first image of crustal structure of the Indo-Myanmar subduction region. Map of subducted Moho across the subduction zone. Physio-chemical composition of the Indian pate and Burmese micro plate. Recent seismicity and geodynamics of the study region. Abstract: We analyzed teleseismic receiver functions of 9 sites to determine the crustal structure beneath the Indo-Burmese subduction region (IBR), which is seismically one of the most active subduction zones of the Indian subcontinent. The receiver function analysis of the primary and reverberated phases allowed us to image the down going Moho beneath the Burmese micro plate parallel to the subducting slab. We observed that this subduction zone is characterized by sharp dip of a thick (˜45 km) crust in the Indian Territory, which steeply bends down to ˜57 km in the Burmese Territory separated by the Churachandpur Mao Fault (CMF). The Imphal valley, located in the central part of the IBR, has a sedimentary thickness of 2.5 km. The Poisson's ratio values correlate well with the tectonic units comprises the subduction region. We observed high Poisson's ratio values throughout the region, which reflects bulk mafic to ultramafic crustal composition. Our observations of Poisson's ratio beneath the IBR reveal that the Indian crust along the IBR is oceanic in nature, which is possibly the Tethyan oceanic crust of Southeast Asia.